2022
DOI: 10.3390/ma15062209
|View full text |Cite
|
Sign up to set email alerts
|

Planar or Biaxial Stretching of Poly(ethylene terephthalate) Fiber Webs Prepared by Laser-Electrospinning

Abstract: In this work, laser-heated electrospinning (LES) process using carbon dioxide laser was explored as an eco-friendly method for producing ultrafine fibers. To enhance the thinning of fibers and the formation of fiber structure, planar or equibiaxial stretching and subsequent annealing processes were applied to poly(ethylene terephthalate) (PET) fiber webs prepared by LES. The structure and properties of the obtained webs were investigated. Ultrafine fiber webs with an average diameter of approximately 1 μm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Latronico et al [ 28 ] investigated the skutterudite thin films and showed that lowering the thermal conductivity can be achieved by laser annealing via adding scattering centers as well as increasing the number of defects. The laser treatment of materials was also successfully used in [ 29 ], where annealing by laser-heated electrospinning was proven to be efficient in producing ultrafine fibers. Heat transfer was even proven to be successful in changing the magnetic state of thin films in [ 30 ], where it was shown that cutting diamond crystals with a laser (532 nm wavelength, 0.5 mJ energy, 200 ns pulse duration at 15 kHz) produced a 20 nm thick surface layer with a magnetic order at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Latronico et al [ 28 ] investigated the skutterudite thin films and showed that lowering the thermal conductivity can be achieved by laser annealing via adding scattering centers as well as increasing the number of defects. The laser treatment of materials was also successfully used in [ 29 ], where annealing by laser-heated electrospinning was proven to be efficient in producing ultrafine fibers. Heat transfer was even proven to be successful in changing the magnetic state of thin films in [ 30 ], where it was shown that cutting diamond crystals with a laser (532 nm wavelength, 0.5 mJ energy, 200 ns pulse duration at 15 kHz) produced a 20 nm thick surface layer with a magnetic order at room temperature.…”
Section: Introductionmentioning
confidence: 99%